POINT DETECTION ANOMALIES IN BAZZONI AURICULAR THERAPY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Auricular therapy is a quite recent form of acupuncture, which was developed originally in France by Dr Paul Nogier. In the last decades, quite a few auricular therapy systems have been presented, the most recent being the Bazzoni auricular therapy. This is an autonomous auricular therapy system, meaning that it does not need to be combined with traditional somatic acupuncture. This system is based on precise protocols and on the precise detection of auricular acupuncture points. This detection procedure is principally carried out using the Pointo Select Digital DT apparatus. In most cases, there are no ambiguities or anomalies in the detection of auricular acupuncture points. However, our recent trial indicates that there is a small, albeit quantifiable, percentage of cases were too many or too few points may be detected, using common detection settings. Although such cases are rare, and do not seem to affect the beneficial result of Bazzoni auriculotherapy, they do seem to present a hereditary tendency.